International branch campus students: choices, experiences and perceptions of employability - Lee, Christine (2016)
The research examined why students chose to study at an international branch campus (IBC) and how they perceived their experiences’ impact on their employability. The research posed a question which has largely been studied using quantitative measures with a few notable exceptions such as Pyvis and Chapman (2007) who investigated offshore Australian programmes. Because quantitative studies cannot capture the underlying complexities encompassing the cultural system and socio-cultural properties influencing the agential powers exercised by the individual, this research attempts to explain student choices and experiences using the concepts of rates of return to education, signalling/screening and identity in the qualitative tradition from a critical realist perspective. The leitmotif of this thesis is the analytical dualism of structure and agency (Archer, 1995) in which the link between these two was an inevitable part of the narrative explaining how structure constrained and enabled participants who as free agents took responsibility for their destinies. Semi-structured interviews were conducted with 31 students from three IBCs.